The Effect of Pressure and Temperature of Residual Life on Separator as Types of Pressure Vessel in “Z” Oil and Gas Field - Reza Fadhlan; Dwi Atty Mardiana; Pri Agung Rakhmanto; Muhammad Taufiq Fathaddin; Rini Setiati; Suryo Prakoso (Journal of Earth Energy Science, Engineering, and Technology, 2022)
Field Z is a mature oil and gas field with several production facilities that have passed their service life design, re-assessment of service life for the critical equipment is needed to carry out. This study focuses on identifying the damage mechanism, determining the residual life assessment, and assessing the effect of pressure and temperature on the residual service life of four separators in field Z. The approach is to recalculate the maximum allowable pressure and the minimum thickness of the separator, estimates the corrosion rate using API 510 and API 581, and estimates the residual life assessment of the separator. The result shows that estimation of corrosion rate with API 581 provide lower value than API 510 due to different methodology. However, the result prove that the operating pressure and temperature of separator will affect to the residual life through minimum thickness and corrosion rate, respectively. The higher operating temperature, the higher corrosion rate. Both of these will reduce the residual life. The calculation estimates that at current operation condition, three of four separators in field Z still can be utilize d at least until next five years. While one separator needs to replace immediately considering to the negative remaining service life.